EKSPERIMENTASI PEMBELAJARAN MATEMATIKA DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DENGAN PENDEKATAN KONTEKSTUAL BERBASIS LESSON STUDY PADA MATERI BANGUN RUANG SISI LENGKUNG DITINJAU DARI GAYA BELAJAR SISWA KELAS IX MTs NEGERI KABUPATEN MADIUN - Umami, Farah; Kusmayadi, Tri Atmojo; Suyono, Suyono (Jurnal Pembelajaran Matematika, 2013)
Abstract:This research aims to find out: (1) which one providing better mathematics learning achievement, Jigsaw type of cooperative learning model with Lesson Study based contextual approach, Jigsaw type of cooperative learning model with contextual approach, or conventional learning, (2) which one providing mathematics learning achievement, the students with visual, auditory, or kinesthetic learning styles, (3) in each learning model, which one providing better mathematics learning approach, the students with visual, auditory, or kinesthetic learning styles, (4) in each learning style, which one providing better mathematic learning achievement, Jigsaw type of cooperative learning model with Lesson Study-based contextual approach, Jigsaw type of cooperative learning model with contextual approach, or conventional learning model.This study was a quasi-experimental research with 3x3 factorial design. The population of research was all IX graders of MTs Negeri of Madiun Regency in the school year of 2012/2013 consisting of 13 school. The sampling technique used was stratified cluster random sampling with 259 students as the sample. The school classification based on the Mathematics score in National Examination of 2010/2011 school year obtained MTsN Kare for the sample with high classification, MTsN Sidorejo Wungu for the one with medium classification, and MTsN Rejosari for the one with low classification. The research instrument used was mathematics achievement test and student learning style questionnaire. Technique of analyzing data used was an umbalanced twoway analysis of variance.The conclusions of research were: (1) the jigsaw type of cooperative learning model with lesson study-based contextual approach provided better learning achievement than the one with contextual approach and conventional learning, while the jigsaw type of cooperative learning model provided the achievement as same as the conventional learning did. (2) the students with visual learning style had learning achievement equal to those with auditory learning style, while both of them had better learning achievement than those with kinesthetic learning style. (3) the students with the visual,auditorial and kinesthetic learning style, the jigsaw type of cooperative learning model with lesson study-based contextual approach provided better mathematics learning achievement than jigsaw type cooperative learning with contextual approach and conventional learning, while the jigsaw type of cooperative learning provided the achievement as same as the conventional learning did. (4) in Jigsaw type of cooperative learning model with Lesson Study based contextual approach, Jigsaw type of cooperative learning model with contextual approach, or conventional learning,, the students with visual learning style provided mathematic learning achievement as same as those with auditory learning style337did, while both of them provided better learning achievement than those withkinesthetic learning style.Keywords: Cooperative Learning, Jigsaw, Contextual Teaching and Learning,Lesson Study, Learning Style.